G476(P) Awareness of gwent children's diabetes website among the children and young people (CYP) and their families. (27th April 2016) - Sakamudi, J; Lynn, S; Pryce, R; Hawkes, D; Hackling, S
Abstract : Background: Gwent Children's Diabetes website was established in 2011. The website has information about team members with their contact details, resources (sick day rules, management of hypoglycaemia, insulin to carbohydrate ratio, correction doses and HbA1c information), local school menus, upcoming events like diabetes holidays and useful links. Aims: To measure the awareness of children and young people (CYP) with diabetes and their families about the website, its usage and their satisfaction. Methods: An audit questionnaire was given to children and their families to fill in at their clinic visits prospectively from September 2014 to March 2015. Results: The total numbers of participants were 41. Among the responders, 90% were above the age of 5 years and the diabetes duration was more than one year among 93% of the responders. The insulin delivery was by basal bolus in 73%, pump therapy in 22% and twice daily injections for the rest. Carbohydrate count was used in 88%. Among the responders, 73% were aware of the website, of which 22% visit the site monthly; 34% visit 2–3 monthly but 17% never visited the website. Up to 70% were checking the information for resources especially local school menus, sick day rules and team member's information. The percentage of the satisfaction was 95% among the responders who has visited the website and 100 percent of them felt that the website was useful. Conclusions: Most of the participants using the website are for resources and are satisfied with the information provided. It is disappointing that despite discussing extensively in clinic that a quarter of patients were not aware of the website and a quarter of those who are aware of the site do not use it. Recommendations: To increase awareness, CYP and their families could be reminded at each clinic visit and during their acute admission to the ward or the acute assessment unit and fluorescent stickers with website information on blood glucose diary.